Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1007/s12210-011-0135-3
|View full text |Cite
|
Sign up to set email alerts
|

Surface formation routes of interstellar molecules: hydrogenation reactions in simple ices

Abstract: It has been a long standing problem in astrochemistry to explain how molecules can form in a highly dilute environment such as the interstellar medium. In recent years it has become clear that not only ion/radical-molecule gas-phase reactions, but also solid state reactions on icy dust grains play an important role in the formation of new species. In order to investigate the underlying processes, laboratory based experiments are needed to simulate surface reactions induced by photon (UV) processing or particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 59 publications
(75 reference statements)
1
24
0
Order By: Relevance
“…Observations revealed that H 2 O is the most abundant constituent of such icy mantles [50]. As gas-phase synthesis of H 2 O turned out to be too inefficient with respect to the detected abundances it is proposed that H 2 O is formed directly on dust grains via surface reactions [e.g., 51].…”
Section: Quantum Tunnelling At the Basis Of Chemical Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations revealed that H 2 O is the most abundant constituent of such icy mantles [50]. As gas-phase synthesis of H 2 O turned out to be too inefficient with respect to the detected abundances it is proposed that H 2 O is formed directly on dust grains via surface reactions [e.g., 51].…”
Section: Quantum Tunnelling At the Basis Of Chemical Evolutionmentioning
confidence: 99%
“…CO ice grows on top of a water-rich layer on interstellar dust grains when the density increases in a dark cloud [50]. This CO ice can be hydrogenated via the successive addition of hydrogen atoms according to the following sequence [58]: CO → HCO → H 2 CO → CH 3 O → CH 3 OH …”
Section: Quantum Tunnelling At the Basis Of Chemical Evolutionmentioning
confidence: 99%
“…This approach makes it possible to derive fundamental and molecule specific parameters, like reaction rates and diffusion barriers, which can then be included in astrochemical models to simulate the ice evolution under much longer timescales (10 5 yr) than accessible in the laboratory (<1 day). Here we follow a bottom-up approach and summarize a representative sample of relevant experiments mainly by our group (see e.g., Fuchs et al 2009;Ioppolo et al 2008Ioppolo et al , 2010aIoppolo et al , 2011aCuppen et al 2010;Romanzin et al 2011), but it should be explicitly stated that other groups -such as the groups of Watanabe, Lemaire and Dulie -are very active in this field as well. These experiments prove that species like H 2 CO, CH 3 OH and H 2 O can be formed at low temperatures by simple hydrogenation (i.e., without the need for thermal, UV or cosmic ray processing) and provide the basic molecular data to simulate their formation on astronomical timescales (e.g., Cuppen et al 2009), even though the ice as a whole is not fully representative for a realistic astronomical ice.…”
Section: Hydrogenation Reactions In Interstellar Ice Analoguesmentioning
confidence: 99%
“…It continues with surface processes induced by H-atom addition reactions and vacuum ultraviolet irradiation, and concludes with experiments studying molecular complexity in ice. The hydrogenation and UV irradiation part of this proceeding are based on highlights presented by Ioppolo et al 2011c, and in a upcoming book chapter on solid state laboratory astrophysics.…”
mentioning
confidence: 99%
“…120 Numerous surface chemistry experiments have validated many of these addition processes. [121][122][123]…”
Section: Cold Grain-surface Reactionsmentioning
confidence: 99%